Localization of impacted maxillary canine teeth: a comparison between panoramic and buccal object rule in intraoral radiography - Nikneshan, Sima; Hosseinzadeh, Mehran; Dehghanpour barooj, Mehrdad; Kheirkhahid, Mahtab (Journal of Dental School, 2019)
Objectives This study aimed to compare the efficacy of panoramic radiography and the buccal object rule in intraoral periapical radiography for localization of impacted maxillary canine teeth. Methods A total of 20 panoramic radiographs depicting 28 displaced maxillary canines were evaluated. The ratio of the mesiodistal width of the impacted canine to the mesiodistal width of the ipsilateral central incisor was calculated and referred to as the canine-incisor index (CII). The height of the crown of each displaced canine was classified in vertical plane relative to the adjacent incisor as apical, middle or coronal. Position of impacted maxillary canines was also determined on two periapical radiographs using the buccal object rule. Surgical exposure and direct observation of impacted teeth were later performed and served as the gold standard. The data were analyzed using SPSS and t-test. Results There was an overlap in the CII range of the buccally (0.78–1.48) and palatally (1.15–1.75) positioned impacted canines. When considering the height factor in the middle and coronal zones, a significant difference was noted between the CII of buccally (0.78–1.1) and palatally (1.15–1.75) positioned teeth enabling determination of their buccolingual orientation (P < 0.05). Conclusion For the impacted maxillary canines located in the middle and coronal zones (90% of cases), the CII of 1.15 and higher represents palatal impaction while the CII smaller than 1.15 represents buccal impaction.